Swedish VET Challenges in the Automation Industry : Lessons learned from the ECVET Project EURIAC - Öhberg, Pernilla [Verfasser] (My University, 2014)
"As far as many young people are concerned, Swedish vocational education and training in automation is a well-kept secret. Working in the industry is not regarded as attractive either by the youngsters themselves or by their parents. The gap between the skills needs of Swedish industry and the students‘ competence level remains wide. The municipality of Kungsbacka in Sweden has attempted to bridge this gap by working with ECVET in the EURIAC project." (authors abstract, BIBB-Doku)
Keywords: I 1.2 Anrechnung im Ausland erworbener Leistungen & Abschlüsse; I 1.4 Berufsbildungsprojekte/Entwicklungsprojekte; Europäisches Leistungspunktesystem; Berufsbildung; Automatisierungstechnik; Schweden; Projekt